OC-124 Centralisation of OG services in the west of Scotland: are we matching the outcomes of the UK national OG audit?. (28th May 2012) - Crumley, A; Bryce, G; Fullarton, G; MacKay, C; Craig, C; Forshaw, M
Abstract : Introduction: The SAGOC report (1997–2000) highlighted the high morbidity and mortality of oesophageal and gastric resections in Scotland. Since then, centralisation into higher volume units has only slowly occurred in Scotland. The UK National Oesophago-Gastric Audit has not included data from Scotland and direct comparisons of outcomes have been lacking. The aim of this study was to assess the surgical outcomes following the establishment of a regional unit in 2007 relative to the outcomes of the National Oesophago-Gastric Audit 2010. Methods: A prospective database (August 2007–December 2011) recorded the demographic details, treatment received, postoperative events and pathology outcomes for all patients undergoing oesophageal or gastric resections. The data were recorded into a Microsoft Excel database and wherever possible the same definitions were utilised as per the National Oesophago-Gastric Audit. Results: 233 patients (males=174 (75%); median age = 66 years) underwent either oesophageal or gastric resections, predominantly for adenocarcinoma (88%). 67% of patients received preoperative chemotherapy. 125 patients underwent oesophagectomy: transthoracic (n=73), transhiatal (n=46), inoperable (n=6). 102 patients underwent gastrectomy: total (n=41), subtotal (n=49), inoperable/bypass (n=12). Six patients underwent wedge resections. 30 day and in-hospital mortality following oesophagectomy was 1.7% and 3.4% respectively, all in patients undergoing transthoracic oesophagectomy and most commonly due to respiratory complications. 30 day and in-hospital mortality following gastrectomy was 3.3% and 5.6% respectively, all in patients undergoing total gastrectomy and most commonly due to surgical complications. 33 patients (14.1%) were admitted to ICU most commonly for respiratory failure and following anastomotic leakage. 37 patients (17.8%) underwent reoperation including endoscopic interventions. Clinical and radiological anastomotic leaks were observed in 12% of oesophagectomies and 10% of gastrectomies. Longitudinal and circumferential margin involvement occurred in 2.6% and 26.3% of oesophageal resections respectively. Longitudinal margin involvement was seen in 11% of gastric resections. Median lymph node was 16 (range=3–54) for all resections. More than six lymph nodes were removed in all oesophageal resections. However, <25 lymph nodes were removed in nearly 80% of gastric resections. Conclusion: The results from this newly established regional unit compare favourably with the outcomes from National Oesophago-Gastric Audit. Significant differences were highlighted in the proportion of transhiatal resections, the absence of minimally invasive surgery and longitudinal margin involvement and lymph node yields for gastric cancer surgery. Competing interests: None declared.